Promotion, Behavior, and Consumption: A Correlation Study between Promotion and Consumerâs Behavior in Indonesian Higher Education - Suwarni, Sini (SOSIOHUMANIKA, 2011)
ABSTRACT: The management of university must be managed as the industry, because the education itself has also been become as an industry. As an industry, including in the human resource development, education must be managed professionally by so many activities such as to produce and to distribute, and to sale the education service to the people or consumer that be done by professional manpower. Meanwhile, in the economic perspectives, promotion is the activity of marketing which informs about the products in order being influenced and remembered by stakeholder. In the activity of promotion, it contains the meaning of communication. In the framework of theoretical perspective above, the objective of the study was to determine the relationship between promotion and consumerâs behavior in Indonesian higher education. The study was conducted at the University of Muhammadiyah Prof. Dr. HAMKA (UHAMKA) in Jakarta on April to June 2006 with a sample of 40 selected randomly. The study concluded that there was a positive relationship between promotion and consumerâs behavior in Indonesian higher education, whereas Y = 37 + 0.955 + 0.767 X at a = 5 meaning with 1 unit increase in promotion will cause 0.767 unit increase in consumerâs behavior in higher education. Key words: management of university, professional manpower, promotion, consumerâs behavior, and higher education in Indonesia.Â About the Author: Dr. Hj. Sini Suwarni is a Senior Lecturer at the Faculty of Education and Teacher Training UHAMKA (University of Muhammadiyah Prof. Dr. HAMKA, Haji Abdul Malik Karim Amrullah) in Jakarta, Indonesia. She can be reached at: aspensi@yahoo.comHow to cite this article? Suwarni, Sini. (2011). âPromotion, Behavior, and Consumption: A Correlation Study between Promotion and Consumerâs Behavior in Indonesian Higher Educationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.1 [Mei], pp.85-92. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 7, 2011); Revised (April 20, 2011); and Published (May 20, 2011). Â  Â